2021
DOI: 10.1101/2021.08.19.21262292
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroresponse to SARS-CoV-2 vaccines among maintenance dialysis patients

Abstract: ImportanceVaccines against SARS-CoV-2 are highly effective in the general population; however, their efficacy may be diminished in maintenance dialysis patients, a population particularly vulnerable to COVID-19 infection and morbidity.ObjectiveWe assessed vaccine response in a national sample of maintenance dialysis patients and identified predictors of response.DesignRetrospective cohort studySetting130 Dialysis Clinic, Inc (DCI) facilitiesParticipantsMaintenance dialysis patients without known prior COVID-19… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…However, this association persisted when the analyses were restricted to only recipients of an mRNA vaccine. This association has been also observed in our prior work (38) and requires further investigation.…”
Section: Discussionsupporting
confidence: 85%
“…However, this association persisted when the analyses were restricted to only recipients of an mRNA vaccine. This association has been also observed in our prior work (38) and requires further investigation.…”
Section: Discussionsupporting
confidence: 85%
“…As previously described, beginning in January 2021, DCI physicians had the option of activating a SARS-CoV-2 vaccine protocol, in which anti-spike IgG antibodies were measured monthly with routine labwork. 4 The chemiluminescent assay ADVIA Centaur XP/XPT COV2G, which measures IgG antibodies against the receptor-binding domain of the S1 subunit of SARS-CoV-2 spike antigen, had received emergency use authorization (EUA) in July 2020. 5,6 This semi-quantitative assay reports a calibrator-established Index Value between 0 and 20 or of ≥20; per manufacturer specifications, titer ≥1 represents detectable antibodies, likely signifying seroresponse.…”
mentioning
confidence: 99%
“…A recent publication showed a similar attenuated antibody response to Ad26.COV2.S vaccine in dialysis patients vaccinated in two dialysis clinics, where after an average follow up of 52 days, 62% of patients had undetected antibody response (<1) (4). A report by Hsu et al, observed 63% of patients vaccinated with Ad26.COV2.S undetected antibody response, however they found that only 7% of patients vaccinated with mRNA vaccines had undetected antibody response (5).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 95%
“…Mysayphonh PharmD 1 , Ines A Dahne-Steuber MA 3 , Curtis Johnson MS 4 , Melanie Pollan PhD 5 , Sandra Alexander BS 6 , Jeffrey G Mulhern MD 7 , Robert J Kossmann MD 1 , Michael S Anger MD 1,2 , Jeffrey L Hymes MD 1 .…”
Section: Linda H Ficociello Dsc 1 Joanna Willetts Ms 1 Claudy Mullo...mentioning
confidence: 99%
See 1 more Smart Citation